Pengaruh Akuntansi Manajemen Strategik dan Kapabilitas Organisasional Terhadap Kinerja Organisasi - Zul Azmi; Isra Desmi Harti (Universitas Batanghari Jambi, 2021)
This study aims to examine the effect of strategic management accounting and organizational capabilities on the organizational performance of hospitality services companies in Pekanbaru City. The data used are primary data obtained from distributing questionnaires to 120 hotel managers at 50 hotels in Pekanbaru City. The research method used is multiple linear regression. The results showed that partially strategic management accounting and organizational capabilities have a significant effect on the organizational performance of hospitality services companies in Pekanbaru City.